Surya Natah dalam Lontar Asta Bhumi (Kajian Kosmologi Hindu) - I Nyoman Subrata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
This article explores the shrine or sacred place in the middle of the yard according to Balinese culture. Balinese buildings have a very complex structure with various other philosophical concepts. Surya Natah is an element of one of the sacred buildings in the middle of the yard that is able to provide energy in every human life. Based on this study, a Hindu cosmological concept was formed which is contained in Lontar Asta Bhumi as a reference or reference in building and positioning a pelinggih that can provide prosperity and prosperity in the yard of the house.